1993
DOI: 10.3146/i0095-3679-20-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Components of Resistance to an Indian Source of Cercospora Arachidicola in Selected Peanut Lines1

Abstract: Cercospora arachidicola Hori is one of the most important foliar pathogens worldwide that limits peanut production in farmers' fields. Earlier screening trials allowed us to identify lines with field resistance to early leafspot, In order to determine the components of resistance of these lines and other lines reported to be resistant elsewhere, 19 peanut genotypes (Arachis hypogaea L.) were evaluated by the detached leaf technique using an isolate of Cercospora arachidicola from the ICRISAT Center in India. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…However, for precise identification of resistant sources, knowledge on components and mechanisms of resistance are the prerequisites for successful breeding programs. Though earlier studies have identified several genotypes for foliar disease resistance (Waliyar et al 1993;Anderson et al 1993;Mehan et al 1996;Singh et al 1997), high degree of resistance to these diseases are not available. Moreover, differential field reaction of recently released peanut cultivars to these diseases is another problem.…”
Section: Introductionmentioning
confidence: 95%
“…However, for precise identification of resistant sources, knowledge on components and mechanisms of resistance are the prerequisites for successful breeding programs. Though earlier studies have identified several genotypes for foliar disease resistance (Waliyar et al 1993;Anderson et al 1993;Mehan et al 1996;Singh et al 1997), high degree of resistance to these diseases are not available. Moreover, differential field reaction of recently released peanut cultivars to these diseases is another problem.…”
Section: Introductionmentioning
confidence: 95%
“…Resistance has different components, including percent defoliation, incubation (time from inoculation until the appearance of lesions) period, latency (time from inoculation until sporulation) period, lesion number and diameter, sporulation, and pod yield Chiteka et al 1988aChiteka et al , 1988bAnderson et al 1993;Waliyar et al 1993Waliyar et al , 1995. Some have argued that as yield is the primary objective in any resistance program, selection based on defoliation would probably be the most appropriate due to its high heritability and the fact that reductions in yield are attributed in large part to premature defoliation in diseased fields (Anderson et al 1991).…”
Section: Breedingmentioning
confidence: 99%
“…Anderson et al (1986) found significant differences among F 1 hybrids between relatively resistant and susceptible parents and argued that resistance to leaf spot may be controlled not only by recessive genes, but also by epistatic and additive alleles. In early leaf spot resistance studies, stability of resistance components has been found to vary across growing regions due to environmental interactions (Waliyar et al 1993;Chiteka et al 1997) as well as to differences in pathogen populations (Waliyar et al 1993) or to both (Chiteka et al 1997).…”
Section: Breedingmentioning
confidence: 99%
“…Resistance to late leaf spot (LLS) (Cercosporidium personatum) has multiple components, including percent defoliation, incubation period, latency period, lesion number and diameter, sporulation, and pod yield (Green and Wynne, 1986;Chiteka et al, 1988aChiteka et al, , 1988bAnderson et al, 1993;Waliyar et al, 1993Waliyar et al, , 1995. High levels of resistance have also been associated with low yield suggesting linkage or pleotropic effects (Iroume and Knauft, 1987), thus breeding for high yielding cultivars with resistance requires this linkage to be broken.…”
Section: Introgression Of Qtls With the Aid Of Molecular Markersmentioning
confidence: 99%